Linguistic Cartography of Migration and Its Impact on the Social and Economic Spheres - Shibina K.M.; P.P. Vijayalakshmi (Communications of International Proceedings, 2020)
The terms diaspora and migration have obtained a broad semantic domain and encompass a diverse array of groups. A lot of people migrate to other geographical spheres in search of job and for better living. The paper probes into the linguistic effect of migration on the lives of people who move from India. An attempt is levied to analyze the relationship between linguistic factor and social, economic, and educational/ professional factors among 60 migrant respondents. Karl Pearson’s Correlation Analysis is used for data analysis. As literature is the mirror of life, the paper also analyses diasporic drawings in literary works, both at national and international levels. To trace the essence of diasporic cartography in the works of Indian-English writers, literary work titled A House for Mr. Biswas by V.S. Naipaul is critically analyzed. Besides, it analyses the theme of migration in Inside Out and Back Again by Thanhha Lai and explores the impact of migration on international subjects.  In short, the paper examines the power of language on the lives of migrant society.
Keywords: Diaspora; Economic; Educational; Linguistic; Migration; Social.